2021
DOI: 10.52813/jei.v10i2.151
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and MSMEs in Indonesia: Impact and Policy Responses

Abstract: Since the first confirmed case of COVID-19 infection in Indonesia in March 2020, the pandemic has hit the economy hard, especially the Micro, Small and Medium-sized Enterprises (MSMEs). This study aims to analyze the extent of the impact of the pandemic on MSMEs and the effectiveness of the government policy measures. Primary data was collected through a questionnaire administered to 2,535 MSMEs in 17 provinces during July–September 2020. The results show that MSMEs already suffered revenue slump within the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 2 publications
1
17
0
1
Order By: Relevance
“…Despite the challenges and hardships faced by MSMEs sector in COVID-19 pandemic, this study has shown that level of well-being is relatively moderate to high, although the case of lower level of well-being is also observed. The MSMEs sector in Indonesia is known to possess the capability to transform challenge into opportunity in regards to sustaining their business through support from various sources, for example during the 1997-1998 and 2008-2009 economic crisis where MSMEs shown their resilience (Gunadi et al, 2021;Sudarmo, 2021)the pandemic has hit the economy hard, especially the Micro, Small and Medium-sized Enterprises (MSMEs. We argue that in the case of MSMEs' well-being in COVID-19 pandemic, those in higher well-being possess the traits of resilience and willingness to adapt, while those in lower level of well-being were facing lack of capability and support to face the challenges of COVID-19 crisis.…”
Section: Figure 1 Swls and Spane-b Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the challenges and hardships faced by MSMEs sector in COVID-19 pandemic, this study has shown that level of well-being is relatively moderate to high, although the case of lower level of well-being is also observed. The MSMEs sector in Indonesia is known to possess the capability to transform challenge into opportunity in regards to sustaining their business through support from various sources, for example during the 1997-1998 and 2008-2009 economic crisis where MSMEs shown their resilience (Gunadi et al, 2021;Sudarmo, 2021)the pandemic has hit the economy hard, especially the Micro, Small and Medium-sized Enterprises (MSMEs. We argue that in the case of MSMEs' well-being in COVID-19 pandemic, those in higher well-being possess the traits of resilience and willingness to adapt, while those in lower level of well-being were facing lack of capability and support to face the challenges of COVID-19 crisis.…”
Section: Figure 1 Swls and Spane-b Resultsmentioning
confidence: 99%
“…The challenges of MSMEs sector in Indonesia can be categorized into financial and non-financial challenges (Gunadi et al, 2021)the pandemic has hit the economy hard, especially the Micro, Small and Medium-sized Enterprises (MSMEs. The diversity of challenges faced by MSMEs sector can be seen in this study with vast number of statements from the respondents.…”
Section: Innovation and Challenges Of Msmes In Covid-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, according to ABDSI (2020), 48.3 percent of MSMEs in Indonesia struggle to sustain their supply chains, 92.6 percent require debt restructuring, and 26.6 percent experience cash flow issues that result in debt the majority of business owners lose the majority of their revenue, while 28% just lose half. Numerous studies have been done to look at how the pandemic has affected MSMEs globally and in Indonesia (see, for example, ILO 2020; ABDSI 2020; Gunadi et al 2021;UNDP & LPEM FEBUI 2020;World Bank & Bappenas 2021;Tambunan 2020). The purpose of this study, however, is to conduct a more thorough investigation of the following issues: (1) the degree to which SMEs' internal strategies are dealing with the pandemic; (2) attitudes toward MSMEs' economic recovery; (3) MSME business recovery strategy; (4) MSME business transformation strategy in anticipating the postpandemic business landscape; and (5) identifying the government assistance required to aid MSME enterprises in their recovery and transformation.…”
Section: Introductionmentioning
confidence: 99%